Practice Before Theory: An Alternative Approach to Piano Pedagogy - Vista-Suarez, Elizabeth Susan (Silliman Journal, 2022)
This paper investigates whether or not there is a difference in learning the mechanics of piano playing between students exposed to “theory before practice” (traditional) and the “practice before theory” (new) approaches. The study was done within one semester where the performances of eight participants who were of probationary status divided into two groups were rated after a semester by their piano teacher, her teaching assistant, sixteen faculty jurors and three junior piano pedagogy students. The results suggest that the ‘practice before theory’ approach to teaching produced a considerable difference in the technical areas of piano study as compared to the older approach, ‘theory before practice.’ Moreover, musical backgrounds and attitudes towards learning of the participants are factors that affected learning. It is recommended that music departments adapt the “practice before theory” approach when teaching entrants who are On Probation and to further monitor the difference in the learning of these students exposed to different piano pedagogy. It further recommends the use of the ‘practice before theory’ approach for other performing disciplines in music such as vocal, instrumental, dance, speech, and theatre; for other learning disciplines in nursing and medicine when learning ‘procedure’; and in different subjects on other learning levels such as early childhood, elementary and high school.